Zawieranie umów przy użyciu wzorców nienormatywnych - Zalewski, Leszek (Wydział Prawa i Administracji UAM, 1989)
The author, noting that general conditions of contracts are widely used in international commercial transactions, focuses his attention on the problems of the so-called battle of forms. The latter includes the situation when e.g. a buyer makes an offer on his own printed form of a contract while a seller accepts that offer on the form whose content is different from the content of the offeror's from. The overwhelming majority of such transactions are carried out without any trouble and thus the question of validity of a contract does not arise. However, if one of the parties intends to evade the performance of his obligation, or if delivered goods are defective, the question appears whether the contract was validly concluded and what is the content of such a contract. The author analyses the ways of eliminating such "battles" adopted in selected legal systems (USA, West and East Germany, Great Britain) and in the light of the United Nations Convention on Contracts for the International Sale of Goods of 1980 and the General Conditions of Delivery of Goods 1968-1975 (in the 1979 version). Finally, the author presents the rules of settling the conflicts of forms in the Polish civil law. It does not regulate separately the above question; instead, general rules of making and accepting offer are applicable. In effect, if an offeree accepts an offer using the from the content of which differs from the content of the offeror's form, the offer is deemed rejected and the new offer, this time made by the offeree, comes into existence. However, if the offeror collects a delivery and pays the price, such a behaviour is regarded as an implied consent (to the offeree's conditions (Art. 60 of the Civil Code). The above solution is advantageous to the party who was the last to send his/her form "the last shot" rule). An objection against the conclusion of a contract on conditions set forth by the other party contained in one or both forms does not change much the above image. However, in some circumstances it may be of importance for the interpretation of the parties declarations of will in the light of Art. 65 of the Civil Code.
Concluding contracts by means of non-normative forms („battle of forms")